Myocarditis Temporally Associated With COVID-19 Vaccination. Issue 6 (10th August 2021) - Rosner, Carolyn M.; Genovese, Leonard; Tehrani, Behnam N.; Atkins, Melany; Bakhshi, Hooman; Chaudhri, Saquib; Damluji, Abdulla A.; de Lemos, James A.; Desai, Shashank S.; Emaminia, Abbas; Flanagan, Michael Casey; Khera, Amit; et al.
Abstract : Supplemental Digital Content is available in the text.